Determining health protection research priorities for Ireland - Claire Gilbourne; Randal Parlour; Máirín Boland; Éamonn O’ Moore; Michelle A. Williams; Rachel Kiersey (Global Public Health)
The study was conducted using a three-round modified e-Delphi approach. An expert panel of 20 members was recruited through the HSE Public Health: National Health Protection Office using purposive sampling. Members of this panel included individuals with the requisite experience and knowledge of health protection research policy and practice who can elucidate research agenda needs and guide practice decisions. This study was designed to identify and rate the importance of health protection research priorities for Ireland. The Health Service Executive (HSE) established a new integrated national health protection service in 2022 to protect the population against all health hazards. The national health protection service is guided by ten strategic objectives within which a culture of research and evidence synthesis is prominently situated. The research team distinguished sixteen broad research priorities for health protection in Ireland. These priorities aligned with the ten strategic objectives within the Health Protection Strategy 2022-2027. This study advances development of a health protection research strategy for Ireland by blending expertise among relevant national and international opinion leaders. The priority areas identified should populate a health protection research agenda during the next five years to address the challenges that face the public health system in Ireland.